Brighter children? The association between seasonality of birth and child IQ in a population-based birth cohort - Vincent W V Jaddoe; Régine P M Steegers-Theunissen; Henning Tiemeier; Albert Hofman; Frank C Verhulst; Nina H Grootendorst-van Mil (BMJ Open)
Objective Season of birth has repeatedly been found to be a risk indicator for adverse neurodevelopmental outcomes. Several explanations for this finding have been put forward but no conclusion has been reached. In the current study, we explored the role of sociodemographic and biological factors in the association between season of birth and child IQ.Design In a prenatally recruited birth cohort (born in 2002–2006), we examined the association between season of birth and non-verbal IQ at age 6 years among 6034 children. We explored how adjusting for socioeconomic status and maternal IQ, childbirth outcomes, pregnancy vitamin D status, nutritional intake, exposure to infections, and child age relative to peers in class changed the relation between season of birth and child IQ.Results We found that spring birth was associated with lower non-verbal IQ (estimate: more than 1 point; β−1.24 (95% CI −2.31 to −0.17), p=0.02; seasonal trend β−0.40 (95% CI −0.74 to −0.07), p=0.02) than birth in summer. Adjustment for different covariates led to a substantial reduction (−65.0% change, in a seasonal trend analysis) of this association. In particular, sociodemographic factors and maternal IQ (−10.0% and −22.5% change, respectively) contributed.Conclusions Season of birth is an indicator of many underlying factors related to child IQ. The observed effects on IQ were small and therefore not of clinical significance.